Simultaneous complexation and extraction of manganese in melissa tea sample by deep eutectic solvent based liquid phase microextraction - Bayraktar, Ahsen; Erarpat, Sezin; Diridiri, Paye Naz; Kus, Kevser; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2024)
Manganese at trace levels cannot be detected by flame atomic absorption spectrophotometer (FAAS) without a preconcentration method. In the presented study, an accurate and sensitive analytical method for the determination of manganese at trace levels in melissa tea samples was established. Deep eutectic solvent based liquid phase microextraction (DES-LPME) was used to preconcentrate the analyte from aqueous medium. Several important parameters were individually optimized to achieve high signal to noise ratio for the analyte in FAAS system. Under the optimum experimental conditions, limit of detection (LOD), limit of quantitation (LOQ) and linear range (LR) for the developed DES-LPME-FAAS system were found as 1.7 mu g/kg, 5.8 mu g/kg and 6.5-202.8 mu g/kg, respectively. Enhancement in detection power was calculated as 112.2 folds by dividing manganese LOD value in FAAS system to value obtained by DES-LPME-FAAS system. Three different melissa tea samples were analyzed by the proposed method to find their manganese content. Percent recovery results for the tea samples ranged between 80.4% and 122.6% with low standard deviation values.
Keywords: Manganese; 5-diphenylthiocarbazone; Melissa tea; Deep eutectic solvent; Flame atomic absorption spectrophotometry; 1; ATOMIC-ABSORPTION-SPECTROMETRY; FOOD SAMPLES; WATER; GREEN; Chemistry; Food Science & Technology